Gerardo Castellanos Lleonart: the mambi consul (1868-1898) (Islas, 2021)
The actions of Gerardo Castellanos Lleonart in the Cuban emancipation process marked the genesis of a revolutionary trajectory that not only developed within the Ten Years’ War framework, but also within Cuban emigration. The objective of this paper is to explain, in all its dimensions, the work of this personality in the fights for the island’s independence and, at the same time, to expand the already existing knowledge about the historiographic conceptions with regard to this stage of the Cuban History. In this sense, numerous bibliographic and documentary sources were analyzed, which allowed us to get acquainted with the most important aspects of his life.
Keywords: Ten Years’ War; Cuban Revolutionary Party; Cuban independence